IMPLEMENTING OF INFORMATION AND COMUNICATION TECHNOLOGY INTO ISLAMIC RELIGIOUS EDUCATION TEACHER AT DI SMP NEGERI 3 TELUKNAGA - Soejono, Sri Rosmalina; Iswadi, Iswadi; Yusari, Nur Indah (Jurnal Visipena, 2024)
Integrating information and communication Technology (ICT) into learning has a very important role in facing the demands of the development of the modern world. This research underlines the role of education and training to increase PAI teachers' competence in ICT. This research aims to describe the level of integration and communication, and technology in PAI teacher training. This research was conducted at SMP Negeri 3 Teluknaga. This research was conducted at SMP Negeri 3 Teluknaga. The population in this study was 23 madrasa PAI teachers and two facilitators participating as informants. The data analysis technique uses the Miles and Huberman interactive model. The research results show that PAI madrasah teachers have integrated ICT but still need to expand to using presentations, especially PowerPoint. Second, age factors and technical problems are the main obstacles in implementing such integration compared to younger teachers, who tend to have a higher level of comfort with new technology because they are more familiar with the use of technology in their daily lives. The availability of ICT facilities at SMP Negeri 3 Teluknaga is classified as good. This research recommends that schools provide a lot of training and support to teachers to improve their mastery of technology and integrate it effectively into the learning process.